Dual-aligned Knowledge Distillation for Class-incremental Multi-fault Diagnosis of an Axial Piston Pump - Wang, Dandan; Liu, Shihao; Zhang, Junhui; Lyu, Fei; Huang, Weidi; Xu, Bing (International Journal of Fluid Power, 2026)
Multi-fault diagnosis of the axial piston pump plays a vital role in ensuring the safety and reliability of modern hydraulic transmission and control systems. Current intelligent fault diagnosis methods demonstrate effective performance but fail to generalize if new fault patterns occur. Simply fine-tuning these models only with newly collected data leads to the catastrophic forgetting problem, whereas retraining a new fault diagnosis model with the entire historical data is both resource-intensive and time-consuming. Therefore, a novel class-incremental learning method based on dual-aligned knowledge distillation is proposed for multi-fault diagnosis of the axial piston pump, which can continually learn new fault patterns and preserve fault diagnosis ability on old fault patterns with a limited amount of historical data. On the one hand, the consistency between output-logits of the previous model and that of the current one is enforced in the incremental learning process to mitigate catastrophic forgetting. On the other hand, intermediate feature relationships with different important weights are aligned to further retain fault diagnosis performance on old fault patterns. Both the comparison experiment and the ablation experiment demonstrate the effectiveness of the proposed method.